2021
DOI: 10.1111/rec.13410
|View full text |Cite
|
Sign up to set email alerts
|

Ground cover and native ant predation influence survival of metamorphic amphibians in a southeastern pine savanna undergoing restoration

Abstract: Longleaf pine savannas historically supported abundant ground cover maintained by frequent fire but little other disturbance. Ground cover creates microclimates with lower temperatures, higher humidity, and increased soil moisture that may benefit wildlife, particularly small vertebrates such as amphibians. Today, most historical pine savannas have had extensive soil disturbance and altered fire regimes resulting in reduced ground cover and altered soil fauna communities including predatory invertebrates. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…For example, Burrow et al . (2021) found that high groundcover availability increased juvenile survival in a southeastern USA pine savanna undergoing restoration. Further, they demonstrated that legacies of historical disturbance can interact with current conditions to influence juvenile amphibian survival (Burrow et al ., 2021).…”
Section: Implications For Amphibian Population Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Burrow et al . (2021) found that high groundcover availability increased juvenile survival in a southeastern USA pine savanna undergoing restoration. Further, they demonstrated that legacies of historical disturbance can interact with current conditions to influence juvenile amphibian survival (Burrow et al ., 2021).…”
Section: Implications For Amphibian Population Managementmentioning
confidence: 99%
“…Differences in ecosystem productivity and heterotroph community structure are often traceable to variations in leaf litter chemistry and associated effects on water chemistry, clarity, and decomposition (Stoler & Relyea, 2011Earl & Semlitsch, 2013;Stoler, Burke & Relyea, 2016;Burrow & Maerz, 2021). Both variation in plant nutrient (i.e.…”
Section: (Vi(4)) Aquatic Habitat Productivity and Biogeochemistrymentioning
confidence: 99%
See 3 more Smart Citations